Mortality from malignant skin melanoma in elderly Brazilians: 2001 to 2016, - Rodrigo Vasconi Sáez Brown; Danúbia Hillesheim; Yaná Tamara Tomasi; Daniel Holthausen Nunes (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Malignant skin melanoma is a serious public health problem, especially among the elderly population. Knowing the dynamics of the mortality rates of this disease in Brazil is essential to support the creation of public health policies. Objective: To analyze the temporal trend of mortality from malignant skin melanoma in elderly people in Brazil, from 2001 to 2016. Methods: This was a descriptive analytical study of mortality rates from malignant skin melanoma in the elderly. The data were obtained from the Mortality Information System, and information related to the population was obtained from the 2010 population census and population estimates from the Brazilian Institute of Geography and Statistics. Mortality coefficients were calculated and simple linear regression analysis of the coefficients was performed by sex and macro-region. Results: A total 12,712 deaths due to malignant skin melanoma in the elderly were registered. The majority (56.8%) occurred in the male population. In females, a tendency of increase in mortality rates due to malignant skin melanoma was observed in the Northeast (p ≤ 0.001), Midwest (p = 0.002), and Brazil as a whole (p = 0.003). In males, an upward trend was observed in all regions, except for the Southeast region. For both sexes, there was also an upward trend in all regions, with the exception of the Southeast region. Study limitations: Secondary databases are directly influenced by the quality of death certificate completion and their heterogeneous scope in Brazilian regions. Conclusion: The increase in mortality indicates a potential public health challenge for the coming decades. The prevention of skin cancer among the elderly should become a priority, mainly through the implementation of preventive measures.